2008
DOI: 10.1177/009286150804200411
|View full text |Cite
|
Sign up to set email alerts
|

Consent Forms, Lower Reading Levels, and Using Flesch-Kincaid Readability Software

Abstract: The US Food and Drug Administration requires the use of a consent form as part of the protection of human subjects in clinical trials. To help increase the probability of consent form comprehension, the biopharmaceutical industry, FDA, National Cancer Institute, and National Institutes of Health often advise developing consent forms between a sixth and eighth grade reading level. Frior studies have examined consent comprehension at different reading levels. However, prior study results are often inconsistent, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 12 publications
(13 reference statements)
0
12
0
Order By: Relevance
“…49 Furthermore, another study showed that increasing readability level, as measured by FKGL, does not enhance comprehension, although the authors still felt that the Microsoft Word version of the FKGL is a useful tool for the initial assessment of a PIL. 50 In contrast, another study which randomised patients to receive a standard information leaflet or a leaflet with a lower FKGL which also added comparative tables and emphasised key information, to promote colorectal screening, found that recognition of information improved with the adjusted text. 51 Peterson improved readability according to automated readability scores but found that most assessors preferred a document which had been edited graphically only.…”
Section: Discussionmentioning
confidence: 99%
“…49 Furthermore, another study showed that increasing readability level, as measured by FKGL, does not enhance comprehension, although the authors still felt that the Microsoft Word version of the FKGL is a useful tool for the initial assessment of a PIL. 50 In contrast, another study which randomised patients to receive a standard information leaflet or a leaflet with a lower FKGL which also added comparative tables and emphasised key information, to promote colorectal screening, found that recognition of information improved with the adjusted text. 51 Peterson improved readability according to automated readability scores but found that most assessors preferred a document which had been edited graphically only.…”
Section: Discussionmentioning
confidence: 99%
“…Data were analyzed using Review Manager (RevMan) v5.2.7. Briefly, we included 14 published randomized controlled trials evaluating modified ICDs for clinical research [11,12,[17][18][19][20][21][22][23][24][25][26][27][28], whether tested in simulated or in real conditions, and we added the results of the present study.…”
Section: Updated Systematic Review Of Improved Informed Consent Formsmentioning
confidence: 99%
“…After reaching the target BrAC, participants read a sexually explicit scenario of approximately 1,600 words at a 5 th -grade reading level as determined by Flesch-Kincaid Grade Level (Kincaid, Fishburne, Roger, & Chissom, 1975; Walters & Hamrell, 2008). The scenario was pilot tested and modified for clarity and realism to participants’ lives.…”
Section: Methodsmentioning
confidence: 99%